Isocyanate toughened pCBT: Reactive blending and tensile properties - T. Abt; M. Sanchez-Soto; A. Martinez de Ilarduya; J. J. Bou (eXPRESS Polymer Letters)
Cyclic butylene terephthalate oligomers (CBT) were reacted in a ring-opening polymerization with three types of isocyanates: a bifunctional aromatic type, a bifunctional aliphatic type and a polymeric aromatic isocyanate. All reactions took place in a batch mixer. The use of 0.5 to 1 wt% isocyanate led to a dramatic increase in elongation at break of polymerized cyclic butylene terephthalate (pCBT), from 8 to above 100%. The stiffness and strength of the modified pCBT, however, were found to slightly decrease. Proton nuclear magnetic resonance (NMR) analysis shows that the formation of thermally stable amide groups is the dominant chain extension reaction mechanism. Gel content measurements suggest a linear structure for samples containing bifunctional isocyanates while pCBT modified with polyfunctional isocyanate exhibited some gel formation at higher isocyanate content. Melting and crystallization temperatures as well as degree of crystallinity were found to decrease with increasing isocyanate content. No phase separation was detected by scanning electron microscopy (SEM) analysis. Moreover, a high degree of polymerization is deduced due to the absence of CBT oligomer crystals.